Suspensive Effect of Claim in Administrative Dispute - Milkov, Dragan; Radošević, Ratko S. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The subject of this paper is the suspensive effect of a claim in an administrative dispute – in comparative and domestic law. Comparative law analysis includes German and Austrian law, having in mind that Serbian judicial control of administration is the closest to their systems. In the explanation of domestic law, we first start from a historical review. The central part of the paper deals with the valid legal regulations in domestic law. The results of the research, which, in addition to legal norms, also includes theoretical explanations and court practice, show a fundamentally different approach to this issue. Different approach leads to a different role of the court in providing this provisional legal protection to the parties. Regardless, however, of the form in which it appears, the question of suspensive effect of a claim in an administrative dispute is always connected with weighing the engaged interests and trying to establish some balance between them.